2021
DOI: 10.1021/acs.iecr.1c03068
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of Biomass by Selected Type-III Deep Eutectic Solvents and Evaluation of the Pretreatment Effects on Hydrothermal Carbonization

Abstract: Hydrothermal carbonization (HTC) is a novel thermochemical conversion that converts wet biomass into energy dense solid fuel. Residual moisture under subcritical conditions reacts with a lignin-cellulose-hemicellulose matrix with the major reactions being identified as dehydration and decarboxylation. Among other reaction parameters (e.g., temperature, time, pressure), biomass morphology often plays a key role in HTC. The hypothesis of this study was enhancing the porous structure of biomass without significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Utilization of such waste biomass for fuel and material development is in dire need, and this has reflected in increasing attention of thermochemical conversions like hydrothermal carbonization (HTC). The solid product of HTC, often called hydrochar, is profoundly studied for applications such as fuel [ 3 , 4 , 5 , 6 , 7 , 8 ], dye and heavy metal removal [ 9 , 10 , 11 ]. When it comes to adsorption or storage, the lack of porosity of hydrochar is often deemed as a bottleneck.…”
Section: Introductionmentioning
confidence: 99%
“…Utilization of such waste biomass for fuel and material development is in dire need, and this has reflected in increasing attention of thermochemical conversions like hydrothermal carbonization (HTC). The solid product of HTC, often called hydrochar, is profoundly studied for applications such as fuel [ 3 , 4 , 5 , 6 , 7 , 8 ], dye and heavy metal removal [ 9 , 10 , 11 ]. When it comes to adsorption or storage, the lack of porosity of hydrochar is often deemed as a bottleneck.…”
Section: Introductionmentioning
confidence: 99%
“…The gaseous byproducts were vented in a fume hood and the solid and liquid phases were recovered through vacuum filtration. The solid conversion was calculated using the following equation 28…”
Section: Catalytic Htt Processmentioning
confidence: 99%
“…The TGA analysis was performed based on ASTM D5142. 28,34 The amount of ash were determined based on the ASTM D1102 method 28 with the use of a muffle furnace. The ash samples were also used to estimate slagging and fouling indices.…”
Section: Characterization Of Solid Residuementioning
confidence: 99%
“…Researchers have identified that, in comparison with gasification or pyrolysis, hydrothermal carbonization (HTC) is an energy‐ and cost‐effective thermochemical technology, which neither requires pre‐drying nor pre‐treatment of the biomass; 17,18 however, some studies suggest that pretreatment (acid pretreatment, alkali pretreatment, deep eutectic solvent pretreatment, etc.) can improve the HTC performance 19,20 . Hydrothermal carbonization takes place in hot, compressed water and induces wet carbonization of the waste products, for example, biomass, plastics, dairy manure, or sewage sludge to synthesize energy‐dense biorefinery feedstock 17,21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…can improve the HTC performance. 19,20 Hydrothermal carbonization takes place in hot, compressed water and induces wet carbonization of the waste products, for example, biomass, plastics, dairy manure, or sewage sludge to synthesize energy-dense biorefinery feedstock. 17,21,22 Despite important literature on the HTC technology, 13,[23][24][25][26][27][28][29][30][31] few studies have been carried out on its operational economic feasibility.…”
mentioning
confidence: 99%